The impact of destination image, shopping value and attributes of local people on attitudes and behaviours of foreigners - Açıkgöz, Fulya (İstanbul Bilgi Üniversitesi, 2018)
[Abstract Not Available]
Destinasyon imajı, alışveriş değeri ve yerel halk özelliklerinin yabancı turistlerin tutum ve davranışları üzerindeki etkileri